Women, Workers, Immigrants: Situated Representations of Trade Union Mobilizations in Italy within the Logistics Sector - Bertoldi, Silvia; Della Puppa, Francesco; Pontarelli, Francesco (PARTECIPAZIONE E CONFLITTO, 2025)
In recent years, logistics workers (who are mostly immigrants) have engaged in various important labour mobilizations. Although it is a male dominated sector, women workers, when present, have played an incredibly active role. This was the case in the mobilizations in Bologna's interport at the sorting, packaging and shipping warehouses of Yoox Net-A-Porter, a luxury e-commerce giant in the fashion industry, and at Italpizza's production plant for the rolling out and topping of frozen pizzas, near Modena, both in Italy. This article will report on a qualitative research aimed at analyzing the working conditions of the immigrant women who took part in the mobilisations and recording their representations of the repercussions and implications that these struggles had on their lives and on the socio-territorial contexts in which they took place. The research revealed that these labour conflicts involving immigrant women extended beyond the workplace, actively involving various groups within their socio-territorial context (associations, collectives, social centers, etc.), encompassing diverse struggles and going beyond purely union-related demands. Furthermore, these collective and self-organized experiences generated spaces for mutual care, the recognition of their agency, and personal and collective empowerment with broad transformative potential. In doing so, they created a sort of "community of struggle," a consequence of the action of "Indie Unions" and the emergence of "Community".